Trends in care practices reflecting parental involvement in neonatal care - Raiskila, Simo (Study of serum leptin in well differentiated thyroid carcinoma: Correlation with patient and tumor characteristics, 2014)
Everyday care practices can facilitate or hinder parents' participation and involvement in neonatal care.